Warm-up exercise suppresses platelet-eosinophil/neutrophil aggregation and platelet-promoted release of eosinophil/neutrophil oxidant products enhanced by severe exercise in men - Wang, Jong-Shyan; Yen, Hsiang-Ling; Yang, Chuen-Mao (Thrombosis and Haemostasis, 2006)
Heterotypic platelet-eosinophil/neutrophil aggregation and subsequent release of eosinophil/neutrophil oxidant products contribute to pathogenesis of conditions such as asthma and inflammatory bowel diseases. This study investigates whether warmup exercise (WUE) affects platelet-eosinophil/neutrophil interaction mediated by high-intensity exercise (HIE). Twenty-three healthy sedentary men performed on three occasions light-intensity exercise (LIE, 40%VO2max for 40 min) and HIE (80%VO2max for 40 min) with and without WUE (40%VO2max for 20 min). Before and immediately after exercise, platelet-eosinophil and platelet-neutrophil aggregation (PEA and PNA), reactive oxygen species production of eosinophils and neutrophils (EROS and NROS) enhanced by platelets, and adhesion molecule expression on platelets, eosinophils, and neutrophils were measured. The results of this study demonstrated that HIE enhanced PEA, PNA, and platelet-induced EROS and NROS, was accompanied by increased expressions of Mac-1 on eosinophils and neutrophils and P-selectin on platelets at 5 dyne/cm2 of shear stress, 100 µg/ml lipopolysaccharide, and 1 µM N-formylmethionyl-leucyl-phenylalanine treatments, whereas the enhancement of HIE on platelet-eosinophil/neutrophil interaction was suppressed by WUE. Conversely, LIE significantly reduced PEA and PNA, suppressed platelet-induced EROS and NROS, and down-regulated eosinophil/neutrophil Mac-1 and platelet P-selectin expressions under various stimuli and shear flow conditions. Moreover, these effects were more pronounced in platelet interaction with eosinophils than with neutrophils. It is concluded that HIE enhances hetero-aggregation, adhesion molecules expressions, and subsequent oxidative bursts mediated by platelets and eosinophils/neutrophils, this effect diminishes after WUE. However, LIE minimizes the risk of thromboinflammation.
Keywords: Warm-up; eosinophil; platelet; inflammation; thrombosis